Investigating the Fundamental Conditions for Quantitative Growth to Obtain High-Quality WS2 Using a Process of Physical Vapor Deposition - Yassine Madoune; Sid Ali Madoune; Luzhi Zhang; Reyadh A. M. Taha; Fuad A. Awwad; Emad A. A. Ismail (Crystals, 2023)
Two-dimensional layered transition-metal dichalcogenides (2D-TMDs) have garnered significant attention due to their layer number-dependent electronic properties, making them promising candidates for atomically thin electronics and optoelectronics. However, current research has primarily focused on exfoliated TMD materials, which have limitations in size, layer number control, and yield. Therefore, a crucial challenge remains in producing large single TMD crystals with precise control over the layer number. A comprehensive understanding and precise control of the growth conditions are imperative to address this challenge. This study systematically investigated key growth conditions, including temperature, precursor flow, growth duration, material quantity, gas flow, and slide position. By optimizing these parameters, we successfully synthesized TMD materials with an impressive size of 850 µm. Notably, we achieved the preparation of monolayer WS2 single crystals on a large scale within a remarkably short duration of 10 min, exhibiting a lateral growth rate of up to 1.4 μm/s, which is comparable to the best-exfoliated monolayers. The findings from our study provide a robust pathway for the rapid growth of high-quality TMD single crystals, facilitating further advancements in this field.